Multidimensional Scaling of Schematically Represented Faces Based on Dissimilarity Estimates and Evoked Potentials of Differences Amplitudes - Izmailov, Chingiz A.; Korshunova, Svetlana G.; Sokolov, Evgeni N. (The Spanish Journal of Psychology, 2005)
This study researches the input of the cerebral occipital and temporal cortex in the analysis of facial configuration and expressive characteristics. Analysis is based on the construction of a spherical model for the differentiation of schematically presented faces with quantitatively altering curvature of the mouth and brows. The model is designed using the method of multidimensional scaling of the dissimilarity judgments between stimuli (faces) and the amplitude of evoked potentials of differences (EPD) between abrupt stimulus changes recorded from the occipital and posterior temporal cortex. Analysis of the structure of the spherical model of facial differentiation depending on the electrode site and the latency of the EPD component within the duration of 120-240 ms has demonstrated that the activity of the occipital and posterior temporal cortex of the right hemisphere is associated with the emotional characteristics of the presented face, whereas facial configuration is reflected in the activation of both posterior temporal cortex and the occipital cortex of the left hemisphere. At all electrode sites maximum information of the emotional expression and configuration is represented in inter-peak amplitude P120-N180. With increasing latency there is increased distortion of the structure of differences in the spherical model of schematically presented faces, which is interpreted as an attenuation of electrical activity associated with the analysis of the emotional expression, which occurs more rapidly than configuration analysis